SOME MEDICINAL PROPERTIES AND ANALYSIS OF GLYCYRRHIZA GLABRA - Abdiravidov Temurbek Abdumannonovich,; Hikmatova Shukrona Ismatovna,; Abzalova Zumrad Jurayevna, (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Objective: Alternative medicine has an important place in the fight against many diseases in human history. The biological activity of Glycyrrhiza glabra L. was investigated in this study. Material and Method: The root parts of the plant were extracted with ethanol. Antioxidant and oxidant potentials were determined using Rel Assay kits. Antimicrobial activity was tested against standard bacteria and fungus strains using the agar dilution method. Antiproliferative activity was determined by MTT test against Lung Carcinoma Cell Line (A549). Result and Discussion: As a result of the studies, the TAS value of the plant was measured as 8.770±0.171, TOS value as 14.590±0.191 and OSI value as 0.167±0.005. Inhibition of the plant extract was observed against standard bacteria and fungus strains at ranging from 50-200 µg/mL concentrations. In addition, it was determined that the plant extract displayed strong antiproliferative activity due to the increase in concentration. As a result of these studies, it has been determined that G. glabra can be used as an important natural antioxidant, antimicrobial and anticancer agent.